Decision-support tool for prevention and control of Rift Valley fever epizootics in the Greater Horn of Africa - Consultative Group for RVF Decision Support (American Society of Tropical Medicine and Hygiene, 2010)
In East Africa, Rift Valley fever (RVF) usually occurs as explosive epizootics with prolonged inter-epidemic periods on the order of 8 to 10 years. The episodic nature of the disease and the rapid evolution of outbreaks create special challenges for its mitigation and control. Following the events of the 2006 and 2007 RVF outbreak in East Africa, decision-makers assembled their collective experiences in the form of a risk-based decision support tool to help guide responses in future emergencies. The premise of the tool is that a series of natural events are indicative of the increasing risk of an outbreak and that actions should be matched to this evolving risk profile. In this manner, investment in prevention and control can be qualitatively optimized. The decision support tool is a living document written through stakeholder input. This publication captures the current tool as an example of risk-based decision support.